Operation of a Photovoltaic Microinverter as Active Power Filter using the single phase PQ Theory and Sliding Mode Control (2017)
Context: Microinverters are widely used in modular photovoltaic installations but its operation with reduced power is limited to inject real power into the grid. One way to optimize the use of microinverters consist of providing them the Active Power Filtering (APF) capability, which allows its use as both distributed generation and compensation unit even under unfavorable conditions of insolation. With this approach, the output stage of the microinverter can provide reactive and distortive components of power in order to compensate power quality defects of a localized load. Method: This paper proposes a non-linear control strategy to integrate the APF function in a singlephase two-stage photovoltaic microinverter. The proposal involves the use of the single-phase P-Q theory to generate the current reference, sliding mode control to achieve a robust tracking of that reference and linear robust control to maintain the power balance regulating the DC-link voltage of the microinverter. The proposed control does not require the use of low-pass filters and in turn uses a recursive average computation improving the general performance of the system. Results: The theoretical approach is validated by means of simulation results in which appropriate levels of harmonic distortion are obtained in the grid-side current for different load types and power levels. The robustness of the control system is tested by applying disturbances in the harmonic content of the load current and its power level obtaining an appropriate dynamic performance adapted to the demands of the application. Conclusions: The main advantage of this proposal is the possibility to add the active filter function to coventional microinverters extending its capability to power conditioning only integrating some algorithms. A simple design method to ensure reliability, robustness and high power quality is detailed.